2013
DOI: 10.1097/hrp.0b013e31827fd8aa
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Quality of Life in Patients with Alcohol Abuse and Dependence

Abstract: Measuring and monitoring QoL during assessment and treatment can add important value to patient recovery, for QoL improves with treatment and successful abstinence. Therefore, targeted, disease-specific assessments of QoL are warranted to address the impairments in the physical, mental, and social domains in alcohol abuse and dependence, thereby improving long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 81 publications
4
41
0
5
Order By: Relevance
“…The gained results showed that the improvement in the quality of physical and mental functioning of alcohol dependent rehab inpatients may take place as a result of therapeutic activity including firstly diagnosis and reduction of depression and anxiety symptoms and secondly minimisation of physical disturbances immediately following the quitting of drinking [42]. Meanwhile, among the homeless an improvement in the same quality of life components could be gained through early interventions cutting down the drinking binges and optimisation of social support [41].…”
Section: ■ Omówienie Wynikówmentioning
confidence: 99%
See 1 more Smart Citation
“…The gained results showed that the improvement in the quality of physical and mental functioning of alcohol dependent rehab inpatients may take place as a result of therapeutic activity including firstly diagnosis and reduction of depression and anxiety symptoms and secondly minimisation of physical disturbances immediately following the quitting of drinking [42]. Meanwhile, among the homeless an improvement in the same quality of life components could be gained through early interventions cutting down the drinking binges and optimisation of social support [41].…”
Section: ■ Omówienie Wynikówmentioning
confidence: 99%
“…Uzyskane wyniki pokazały, że poprawa jakości funkcjonowania fizycznego i psychicznego osób uzależnionych od alkoholu leczonych stacjonarnie może nastąpić w wyniku działań terapeutycznych, w których należałoby po pierwsze diagnozować oraz redukować objawy depresyjne i lękowe, po drugie -minimalizować zaburzenia somatyczne zaraz po odstawieniu alkoholu [42]. Z kolei u osób bezdomnych poprawę tych samych komponentów jakości życia można byłoby uzyskać przez wczesne interwencje przerywające ciągi picia i optymalizację wsparcia społecznego [41].…”
Section: ■ Omówienie Wynikówunclassified
“…In persons aged 20–39 years, 25% of deaths are caused by alcohol addiction 4. Alcohol-related diseases such as hepatitis, pancreatitis and various psychiatric disorders (eg, depression) cause a reduced quality of life 5 6. Negative social consequences of alcohol dependence (AD) include unemployment and social isolation.…”
Section: Introductionmentioning
confidence: 99%
“…One review found that reductions in alcohol use markedly increase HRQL for alcoholics (Donovan et al, 2005), even if the HRQL for those reducing alcohol intake is still lower than HRQL for normative or abstaining populations (Donovan et al, 2005; Saarni et al, 2008). Alcohol abuse treatment programs also improve HRQL (Srivastava & Bhatia, 2013; Ugochukwu et al, 2013). Further, simple interventions like motivational aid or advice can help reduce alcohol use among heavy drinkers, which improves HRQL (Kraemer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%